The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.4143/crt.2018.356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of PALB2 Germline Mutations in Early-onset and Familial Breast/Ovarian Cancer Patients from Pakistan

Abstract: Purpose Partner and localizer of BRCA2 ( PALB2 ) is a breast cancer susceptibility gene that plays an important role in DNA repair. This is the first study assessing the prevalence of PALB2 mutations in early-onset and familial breast/ovarian cancer patients from Pakistan. Materials and Methods PALB2 mutation screening was performed in 370 Pakistani patients with early-onset and familial breast/ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The present study included 302 early-onset and familial breast cancer patients with ER positive and/or PR positive tumors. All study participants were tested negative for pathogenic variants in BRCA1, BRCA2 [17,18] and about 60% for pathogenic variants in PALB2 (n = 187), TP53 (n = 180), CHEK2 (n = 168), and RAD51C (n = 168) [13][14][15][16] (Muhammad U. Rashid, unpublished TP53 data). We categorized study participants into four risk groups based on age at cancer diagnosis or family history of breast and/or ovarian cancer (Table 1) [17].…”
Section: Study Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…The present study included 302 early-onset and familial breast cancer patients with ER positive and/or PR positive tumors. All study participants were tested negative for pathogenic variants in BRCA1, BRCA2 [17,18] and about 60% for pathogenic variants in PALB2 (n = 187), TP53 (n = 180), CHEK2 (n = 168), and RAD51C (n = 168) [13][14][15][16] (Muhammad U. Rashid, unpublished TP53 data). We categorized study participants into four risk groups based on age at cancer diagnosis or family history of breast and/or ovarian cancer (Table 1) [17].…”
Section: Study Subjectsmentioning
confidence: 99%
“…umd.be/HSF3/), GeneSplicer (http://ccb.jhu.edu/software/ genesplicer/), and SpliceSiteFinder-like (http://www.umd. be/searchSpliceSite.html) for splice-site and intronic variants [14]. In case of any disagreement between clinical and functional evidence, the clinical evidence was considered more convincing.…”
Section: Variant Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to these two sets of genes, PALB2 (15%) and RAD51C (8%) showed significantly higher proportions than previous findings for young women with breast cancer carrying positive mutations (1%) [8]. Recent studies have reported that PALB2 represents 1%-4% [15][16][17] of total mutations in early-onset breast cancer. Our study found that, overall, PALB2 accounted for 2% and RAD51C for 1% of the germline pathogenic variants.…”
Section: Pathogenic Variants In Young Women With Breast Cancermentioning
confidence: 57%
“…Indeed, germline mutations in BRCA1 and BRCA2 are the most important risk factors for hereditary breast and ovarian cancer and contribute to 5%-10% of breast cancers, being inherited in an autosomal dominant manner (Shih et al, 2002;Skol, Sasaki, & Onel, 2016). Besides BRCA1/2 genes, other cancer predisposition genes (ATM,PALB2,TP53,BARD1,CHEK2) are also implicated in hereditary breast cancer (Elledge & Allred., 1998;Meijers-Heijboer et al, 2002;Usman, Khan, Muhammad, Loya, & Hamann, 2018;Walsh & King., 2007).…”
Section: Introductionmentioning
confidence: 99%